Human Security for Sustainable Development in Nigeria: The Role of Information and Communication Technology (ICT) - Muhammad Bashar, Lukman (Covenant Journal of Informatics and Communication Technology, 2017)
Human security is needed in response to the complexity and the interrelatedness of both old and new security threats ranging from chronic and persistent poverty to ethnic violence, human trafficking, climate change, health pandemics, international terrorism, and sudden economic and financial downturns. The paper: Human Security for Sustainable Development in Nigeria: The Role of Information and Communication Technology (ICT) looks at the role of improved technology in human security and development, analyzes technology utilization in addressing human security and development issues in Nigeria. It recommends among others increasing the accessibility of information technology to reduce the threat to sustainable livelihood.Â